Pendampingan Pohlaksar Camar Laut dalam Adopsi Teknologi Digital untuk Perluasan Akses Pemasaran - Rahmawati Rahmawati; Nabila Ukhty; Akbardiansyah Akbardiansyah; Eka Lisdayanti; Safnarita Safnarita (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
Conventional marketing practices, limited digital literacy, and the underutilization of digital media continue to constrain market expansion and competitiveness among fishery product processors. This community engagement program aimed to strengthen the digital marketing capacity of Poklahsar Camar Laut members through a participatory approach involving needs assessment, training, mentoring, and evaluation. Program effectiveness was assessed using pre- and post-training evaluations, observation of digital media utilization, and technology adoption indicators. Results showed a substantial increase in participants’ knowledge, from approximately 30–40% before training to 80–90% after the intervention. Technology adoption reached 80%, digital marketing understanding 90%, independent digital media management 70%, promotional content consistency 60%, and program sustainability 70%. The program improved participants’ ability to manage social media, create promotional content, and utilize digital platforms for marketing communication and customer network expansion. These findings indicate that practice-based mentoring effectively supports the transition from conventional to digital marketing, contributing to enhanced marketing capacity, wider market access, and the sustainability of fishery-based businesses.